New insights into the behavioral structure of Pikler educators: An application of T-pattern detection and analysis with THEME - Belza, Haizea; Portell, Mariona; Herrán, Elena; Anguera, M. Teresa (Frontiers in Psychology, 2023)
The recent generalization of early childhood schooling has given rise to a need for the development of rigorous, specific training programs aimed at early education professionals (0-3 years of age). This work emanates from the unique nature of Pikler-Lóczy education as a reference for early childhood education centers, and its expertise in providing quality care in an everyday classroom situation. The aim of the study is to use T-pattern detection and analysis, within the framework of observational methodology, to identify relevant aspects of the choreography followed by Pikler educators during breakfast, and thus provide substantial material with a view to creating a training plan. Two expert educators in Pikler-Lóczy education were directly and systematically observed in their own classrooms, following a nomothetic, follow-up and multidimensional design. The observation instrument underwent a molarization process so that the detected elements would be more significant and understandable for novice educators. Using THEME, the invariant aspects of the educators’ behavior were analyzed. The results show: on the one hand, changes expected in T-patterns in accordance with the observation instrument molarity; and on the other hand, stability in terms of the comparison between the two educators. These results help us to identify the complex structure of the breakfast choreography, and how educators establish interaction with children. In addition to specific issues pertaining to Pikler-Lóczy education, the conclusions highlight the advantages of using T-pattern analysis within the framework of observational methodology, in order to dissect a mealtime routine in its natural context, and explain components of early childhood education intervention that satisfy basic childhood needs. This constitutes a starting point from which to generate instructive material for the training of professionals working in early education.